موقع ويب وتطبيق تجارة إلكترونية لفئة الحرفيين - : : المصري بيان , شيبة ريم , شيحاني محمد الأمين , نسيب عماره (university of eloued جامعة الوادي, 2024)
يواجه العديد من الحرفيين تحديات كبيرة في تسويق منتجاتهم اليدوية والوصول إلى قاعدة واسعة من الزبائن، مما يحد من فرص نموهم وربحهم. تشمل هذه التحديات نقص الموارد التقنية، ضعف القنوات التسويقية، وصعوبة الوصول إلى العملاء المحتملين في الأسواق المختلفة. يهدف مشروعنا إلى إنشاء منصة إلكترونية متخصصة لتسهيل بيع وتسويق المنتجات اليدوية. تتمثل الفكرة الرئيسية في توفير واجهة سهلة الاستخدام تربط بين الحرفيين والعملاء، مما يسهل عرض وشراء المنتجات بفعالية. لتحقيق هذا الهدف، سنطور منصة متقدمة تستخدم أحدث التقنيات لضمان تجربة مستخدم متميزة، مع تقديم دعم فني مستمر لمساعدة الحرفيين في تحسين أدائهم التسويقي. Many artisans face significant challenges in marketing their handmade products and reaching a broad customer base, which limits their growth and profit opportunities. These challenges include a lack of technical resources, weak marketing channels, and difficulty in accessing potential customers in various markets. Our project aims to create a specialized online platform to facilitate the sale and marketing of handmade products. The main idea is to provide an easy-to-use interface that connects artisans with customers, making it easier to showcase and purchase handmade products effectively. To achieve this goal, we will develop an advanced platform using the latest technologies to ensure an exceptional user experience, along with continuous technical support to help artisans improve their marketing performance.
مدكرة ليسانس اعلام الي
Keywords: تجارة إلكترونية | حرف يدوية